CERTIFIED INDEPENDENT STUDY PROGRAM AT PT. LACORRE LOKA MAYA AS A STUDENT LEARNING FACILITY IN THE FIELD OF DIGITAL FASHION EXPORT - Gatri Letar Hutabarat (RADJA PUBLIKA, 2024)
The economy includes the production, distribution and consumption of goods and services, as well as the resource allocation system in a country. Economic growth is important in the development and welfare of society. International business refers to cross-border economic activities that involve the exchange of goods, services, or information. The fashion industry in Indonesia shows strong resilience to economic changes. Exports, one of the drivers of economic growth, will experience a decline in November 2023. To support exports, especially by SMEs, training and digitalization are needed. Certified Independent Study is part of the Independent Campus program which aims to provide opportunities for students to learn and develop themselves through activities outside of the lecture class, but is still recognized as part of the lecture. PT Lacorre Loka Maya (LaCorre) collaborates with the Export School in the Digital Fashion Export program, aimed at creating new exporters from among students. This program is carried out in a hybrid manner with learning, practical and exhibition activities. Students learn various aspects of exporting through mentoring, export lectures and practicums. The results of this program include increasing knowledge, attitudes, general and specific skills in exports, with the aim of making Indonesia the world's main exporter by 2045.